(untitled) (JBN (Jurnal Bedah Nasional), 2025)
Aim: This study examines the relationship between obesity, intraoperative blood loss, and systemic inflammatory responses (NLR and CRP) concerning perioperative complications in colorectal cancer surgery. Methods: A retrospective analytical observational study was conducted on 96 patients who underwent colorectal cancer surgery from January 1 to August 31, 2023. The analysis included obesity history, intraoperative blood loss, NLR, and CRP levels, using descriptive statistics, Chi-Square tests for Odds Ratios (OR), and logistic regression for adjusted odds ratios. Results: The study found a 38.5% complication rate in patients with BMI ≥25 kg/m² (OR=35) and a 29.5% rate in those with CRP >150 mg/L (OR=7). Patients with NLR >3 had a 21.1% complication rate (OR=1.3), while those with intraoperative blood loss >800 mL faced an 83.3% complication rate (OR=36). Logistic regression indicated that obesity and CRP are independently associated with major complications. Conclusion: Obesity, intraoperative blood loss, NLR, and CRP collectively influence major perioperative complications, with obesity and CRP being the most significant independent factors in colorectal cancer surgery.